STUDY OF BINDING PECULIARITIES OF ETHIDIUM BROMIDE AND METHYLENE BLUE WITH DOUBLE-STRANDED RNA (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The paper presents the results of studies on the interaction of intercalators ethidium bromide (EtBr) and methylene blue (MB) with synthetic double-stranded (ds) ribonucleotide ds-poly(rA)-poly(rU) at a solution ionic strengths of 0.02, 0.04 and 0.1 M. These results revealed that poly(rA)-poly(rU) has a relatively unstable structure at the ionic strengths μ$≤$0.02 M, which leads to the interaction of the mentioned ligands with this polynucleotide. EtBr affinity for ds-poly(rA)-poly(rU) was revealed not to depend on the ionic strength of the solution, while the affinity of MB for this polynucleotide depends on this factor, as well as on the structural state of the polynucleotide.
Keywords: synthetic polyribonucleotide; intercalator; ethidium bromide; methylene blue; complex; melting parameters